Peningkatan Daya Saing UMKM Kerupuk Ibu Supatmah Melalui Pendaftaran Halal, NIB, Shopee dan Rebranding - Afif Wahyu Lestari; Sri Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
Karimunjawa is a place famous for its natural beauty, attracting many local and foreign tourists. In addition to its tourism potential, Karimunjawa also has a community of MSMEs in various sectors, one of which is the fish cracker processing sector. However, from the field observations conducted by the community service team, it was found that many MSMEs still experience problems with productivity, weak product branding, and customers having difficulty finding business locations. One of the MSMEs experiencing this is the Karimunjawa specialty cracker MSME owned by Mrs. Supatmah. The community service team implemented several programs to address these issues, including registering the business address on Google Maps, obtaining halal certification and legal NIB registration, creating a Shopee account, and strengthening branding through product logos and rebranding on labels and packaging. Based on the evaluation results, the assisted SMEs experienced increased customer trust, expanded market reach, and were able to compete with similar SMEs that were already established.